Variables for Determining Manager Attitudes in Debt Funding: Study on SME in Sleman Yogyakarta - Nilmawati, N; Satoto, Shinta Heru; Nurrohim KP, Hasa (Universitas Muhammadiyah Surakarta, 2019)
Purpose: This study aims to examine the effect of variable economic orientation variables, experience with debt suppliers (creditors), financial knowledge, and the need for controls to explain the financial attitude of debt financing with family commitment as a moderating variable and company age as a control variable.Methodology: The method of data collection is done by survey, by sending a questionnaire. Respondents in this study consisted of 100 owners or managers of small and medium enterprises in the Sleman Regency of Yogyakarta. The analytical tool used in moderated regression. Results: Test results show that positive experience with creditors has a positive and significant influence on attitudes related to debt use. While the orientation of economic objectives, financial knowledge and the need for control cannot explain the effect on attitudes related to debt. This research also proves that the moderating variable of family commitment weakens the positive effect of experience with creditors on the positive attitude of managers in debt financing.Application / Originality / Value: This study includes the need for control variables in a model that links economic orientation, financial knowledge, and financial experience with managers’ attitudes in debt financing for family businesses that have not been considered in previous studies.